A thematic analysis of factors influencing decisions to use physical restraint in acute mental health settings : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Philosophy in Nursing, Massey University - Edgar, Murray James (Massey University, 2007)
This study investigates the factors that influence nurses' decisions to use physical restraint or to attempt alternative interventions within acute mental health inpatient settings. The objective was to better understand the background to these decisions in the hope that this will lead to the development of more consistent and justifiable approaches to challenging behaviour displayed by some mental health patients. Eight nurses working or recently working in acute mental health services in two different District Health Boards were interviewed using a semi-structured interview technique. The sample was purposive, with participants being asked about their experiences with physical restraint, using specific events from their clinical practice. These interviews were then reviewed by the researcher and note taken of areas for further exploration or clarification. A second interview focussed on the areas identified as of particular interest to this research. 32 events of restraint use or near-use were related to the researcher, giving a significant amount of data for analysis. A thematic analysis approach was used to identify and examine themes within the data. The central thesis emerging from the data and its analysis is that much of what influences nurses' decisions relates to intrinsic factors such as their attitudes towards the patients in their care, whether the patients are appropriately domiciled in mental health services, and assessments of the causes of the challenging behaviour. The importance of working as a team and trusting colleagues emerged as a strong yet previously under-researched theme. Implications for nursing practice are discussed. Particular emphasis is placed on the further development of Calming and Restraint programmes for nurses working in acute mental health settings. The need to address the background attitudinal factors from both a training and service delivery perspective is strongly evident.
Keywords: Psychiatric hospital patients; Psychiatric hospitals; New Zealand; Physical restraint; Emergency services